USM, NUT SETS UP JOINT GIKAKU TECHNOLOGY CENTRE TO INCREASE COOPERATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 29 May 2015 - Universiti Sains Malaysia (USM) continues to increase its international cooperation with Nagaoka University of Technology (NUT) Japan in academic and research collaborations through the establishment of the NUT-USM Gikaku Technology Centre.